2012
DOI: 10.2967/jnumed.111.090340
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Amyloid PET with Florbetapir F 18 in Patients with Alzheimer's Disease and Cognitively Normal Subjects

Abstract: The objectives of this study were to examine the effective dose range and the test-retest reliability of florbetapir F 18 using, first, visual assessment by independent raters masked to clinical information and, second, semiautomated quantitative measures of cortical target area to cerebellum standardized uptake value ratios (SUVr) as primary outcome measures. Visual ratings of PET image quality and tracer retention or b-amyloid (Ab) binding expressed as SUVrs were compared after intravenous administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
305
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 348 publications
(315 citation statements)
references
References 29 publications
9
305
1
Order By: Relevance
“…The software packages used in this study, MIM (MIMneuro®), Siemens (Siemens syngo.PET Amyloid Plaque) and Hermes (Hermes Brain Analysis Software Suite™ BRASS, 2.0; CE 0413), are all commercially available and approved in the US and EU for visual examination and quantitation of PET images, with specific routines designed to quantitate 18 F-florbetapir PET images. Although the individual packages use different proprietary algorithms to perform the quantitation, the three packages share the following features:…”
Section: Software Packagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The software packages used in this study, MIM (MIMneuro®), Siemens (Siemens syngo.PET Amyloid Plaque) and Hermes (Hermes Brain Analysis Software Suite™ BRASS, 2.0; CE 0413), are all commercially available and approved in the US and EU for visual examination and quantitation of PET images, with specific routines designed to quantitate 18 F-florbetapir PET images. Although the individual packages use different proprietary algorithms to perform the quantitation, the three packages share the following features:…”
Section: Software Packagesmentioning
confidence: 99%
“…PET imaging ligands including Pittsburgh compound B ( 11 C-PIB) [2], 18 F-florbetaben [3], 18 F-flutemetamol [4] and 18 F-florbetapir [5] have been developed for estimation of cortical beta amyloid (Aβ) neuritic plaque deposition, a hallmark pathology, and a required element for the evaluation of neuropathological changes in patients with Alzheimer's disease (AD) [6]. As shown by their respective package inserts/summaries of product characteristics, as well as the published literature [7][8][9], reader accuracy in the pivotal trials for the 18 F-labeled agents averaged close to 90% for discriminating patients found at autopsy to have no or sparse neuritic plaques (amyloid-negative, Aβ−) from those found to have moderate to frequent plaques (amyloid-positive, Aβ+). However, as might be expected, within each of these development programs, there were individual readers with sensitivity or specificity values below the average, and in some with values below 80%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold lines in Figure 4 indicate the mcSUVr threshold that best classified positive and negative cases obtained from the ROC analysis (1.10 for whole cerebellum, 1.28 for cerebellar gray matter, 0.78 for pons, and 0.68 for the centrum semiovale). The threshold of 1.10 determined on the basis of the ROC analysis in this study is identical to the threshold selected for no detectable amyloid in a prior study (19), based on the upper limit of the 2-sided 95% confidence interval for YCNs. Using the whole cerebellum as a reference region, there was clear classification with no overlap between the 74 YCN/20 pathologynegative group (black and blue dots) and 39 pathology-positive subjects (red dots) except for a single pathology-positive case, clinically diagnosed as AD, quantified with a mcSUVr of 1.02.…”
Section: Resultsmentioning
confidence: 68%
“…Thus, if the actual signal change during disease progression was similar or better to what is seen with FDG (although in the opposite direction), tau PET may actually provide superior performance as a progression biomarker. Compared to amyloid PET, which also has excellent test-retest reproducibility [7] but appears to reach a kind of plateau already very early during disease progression with little further change and poor correlation with clinical disease severity, tau PET clearly looks more promising.…”
mentioning
confidence: 99%